Effect of emulsification processes on the stability of Pickering emulsions stabilized by organomontmorillonites. Issue 7 (3rd July 2017) - Zhou, Daojin; Zhang, Zepeng; Tang, Jialun; Zhao, Jiali; Liao, Libing
ABSTRACT: In this paper, effect of emulsification processes on the properties of Pickering emulsions stabilized by organomontmorillonites (OMts) was studied. Results of micro-morphology and X-ray diffraction showed that the structure of OMt in emulsion depended on the emulsification processes and had an effect on the stability of emulsion. We propose a schematic diagram to reveal the relationship between emulsification processes-OMt laminates structure-stability of Pickering emulsion. In emulsion prepared by ultrasonic, OMt showed uniform dispersion, loose structure, and irregular crystalline. In emulsion prepared by vortex mixing method, OMt illustrated stacking and coagulation structure. In emulsion prepared by microwave method, OMt showed interacting structure and had a little interaction with oil/water interface, and thus the properties of emulsion prepared by microwave was weakly related to oil/water ratios. Emulsification processes had a profound effect on the structure of OMt and stability of Pickering emulsion, which can be used as a trigger to prepare emulsion for various applications. GRAPHICAL ABSTRACT: